THE REALTIONSHIP BETWEEN ACADEMIC BURNOUT AND ACADEMIC PROCASTINATION OF HIGH SCHOOL STUDENTS IN CILACAP - Endang Rifani (PROCEEDING AL GHAZALI International Conference, 2023)
Academic procastionation is the behavior of delaying to complete academic tasks. Academic procastination can be caused by psychological conditions that are emotionally exhausted. This study aims to determine the realtionshin between academic burnout and academic procastination of high school students in Cilacap. This research is a quantitative correlation study and the data were analyzed using descriptive analysis. The research subjects used cluster random sampling involving 100 high school students in Cilacap. The result of the study using the person product moment = correlation test, showed rxy = 0.624with the significance value of p = 0.0000 (p < 0,05) indicating that the hypothesis is accepted. So that the result reveal there is significant positive relationship between academic burnout and student academic procastination.